Orbital varix presenting with enophthalmos and intermittent proptosis: a case report - Saini, Varun; Bhattacharya, Shruti; Raina, Usha K.; Goyal, Jawahar Lal (International Journal of Advances in Medicine, 2022)
We report the case of a 22-year-old male, presenting with right enophthalmos and intermittent exophthalmos observed after valsalva maneuver. Orbital imaging revealed a retrobulbar vascular lesion with multiple phleboliths suggestive of orbital varices. On magnetic resonance angiography, no obvious feeder vessel could be delineated. We decided to manage the patient conservatively, in the absence of complications such as proptosis with corneal exposure, optic nerve compression, orbital hemorrhage. Orbital varix is a low flow vascular anomaly which generally presents with an intermittent exophthalmos. Development of enophthalmos associated with orbital varices as in our case, is very rare.